The Rietbeg Museum and the Antiquities Dealer - Beier, Ulli (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent)
Copyright held by Iwalewahaus, CBCIU.
Keywords: Transcription; Museums; Books; Antiquities Dealer